Paleogenomics of the Plague Agent and Prospects for Paleogenomic Studies in Russia - G. A. Eroshenko; E. F. Batieva; V. V. Kutyrev (Проблемы особо опасных инфекций)
The review contains information on paleogenomic studies of the plague pathogen, Yersinia pestis, covering the prehistoric epoch, the periods of the first and second plague pandemics, epidemics and outbreaks of plague of the late XIX–XX centuries. We have summarized the data on the reconstruction of ancient Y. pestis genomes of the Late Neolithic, Bronze and Iron Ages, the Justinian Plague epidemic of the first plague pandemic, the Black Death epidemic and the subsequent epidemics of the second plague pandemic of the XIV–XVIII centuries, as well as on tracing the pathways of plague propagation waves in Eurasia and the course of plague agent evolution with the formation of a vector-borne transmission route with the help of arthropods. We present the results of our own research of Y. pestis genomes from the key sites of formation of etiological agents of the first and second plague pandemics in the Tien Shan Mountains, historical outbreaks in the Northern and North-Western Caspian sea region and other regions of Russia and adjoining countries in the late XIX–XX centuries. The paper discusses the areas of the Caucasus, Crimea, Northern Caspian, Siberia, and Tien Shan in the territory of Russia and neighboring states that are promising for national paleogenomic studies of plague.